MicroRNA-590-3p promotes cell proliferation and invasion by targeting inositol polyphosphate 4-phosphatase type II in human prostate cancer cells - Haiwen Chen; Qidong Luo; Hongliang Li (Tumor Biology)
Inositol polyphosphate 4-phosphatase type II emerges as a tumor suppressor in prostate cancer, and its loss of expression is associated with poor prognosis for prostate cancer. However, the mechanism of downregulation of inositol polyphosphate 4-phosphatase type II in prostate cancer development has not yet been fully clarified. In this study, microRNA-590-3p was found to be upregulated in both prostate cancer tissues and cell lines. Overexpression of microRNA-590-3p by microRNA-590-3p mimics promoted prostate cancer cell proliferation and invasion and accelerated the growth of xenografted tumors, while microRNA-590-3p inhibitors contributed to inhibition of cellular proliferation and invasion as well as tumor growth. A dual-luciferase reporter assay and expression analysis further confirmed that inositol polyphosphate 4-phosphatase type II was a direct target of microRNA-590-3p. Enforced expression of microRNA-590-3p led to repression of inositol polyphosphate 4-phosphatase type II messenger RNA and protein expression, as well as upregulation of p-Akt, p-FoxO3a, and cyclin D1 and downregulation of p21 expression in prostate cancer cell lines. Overexpression of inositol polyphosphate 4-phosphatase type II could reduce microRNA-590-3p-induced cell proliferation and invasion as well as tumor growth, and decrease microRNA-590-3p-mediated upregulation of cyclin D1 and downregulation of p21 expression in prostate cancer cells. Taken together, our findings reveal that microRNA-590-3p is a potential onco-microRNA that participates in carcinogenesis of human prostate cancer by suppressing inositol polyphosphate 4-phosphatase type II expression and involving the Akt/FoxO3a pathway. MicroRNA-590-3p may represent a potential therapeutic target for prostate cancer patients.